PENGARUH KOMBINASI MODEL PAP DAN TTW TERHADAP HASIL BELAJAR SISWA SMA SUBMATERI SISTEM SARAF MANUSIA - Selvia, Delvi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed to find out the influence of combination picture and picture and think talk write model on students’ learning outcomes in the submaterial of Human Neuron System grade XI SMA Panca Bhakti Pontianak. This was a quasi-experimental research with nonequivalent control group design. The samples are XI Science 1 as an experimental group and XI Science 2 as the control group. The instrument was a multiple choice test (20 items). The data analysis showed an average score of students’ learning outcomes in experiment group was 15,81 while in control group was 14,09. From the t’-test, obtained t’count >ttable = 4,20>2,73, there was a significant difference of students’ learning outcomes. The Effect size score was 0,54 (medium category) and provided a contribution of 20,54%, so this model had a positive influence. Keywords: influence, picture and picture and think talk write, submaterial of human neuron system, learning outcomes